Productivity of females loggerhead from Cabo Verde Islands - Lozano-Fernandez, Matías; López-Jurado, Luis Felipe (2016)
The nesting colony of Caretta caretta has been recently described for the island of Boavista (Cabo Verde, 500 km off the coast of Senegal, Western Africa, FIGURE 1). Although more data is needed, it represents one of the most important populations in the North Atlantic (Brongersma, 1982; López-Jurado & Andreu, 1998; Ross, 1995). Since 1998, a tagging and management campaign was established in Boavista to study this nesting population. We present next data on reproductive biology of nesting females of Caretta caretta in Boavista during the year 2000 nesting season, in which we obtained twice as much than those tagged in 1998 and 1999 seasons; we also found some recaptures of females from preceding years, our first data on remigration interval.